Peningkatkan Kreativitas Pemuda Rajawali Peduli Lingkungan dalam Pengolahan Sampah Anorganik di Kelurahan Jogosari Pandaan Pasuruan - Nisa, Khoirun; Rosyidi, Khafizh; Mufidah, Nur; Mudrika, Siti; Nihayatus S., Ulin; Maulida, Rizka; Dwi W., Sri; Subchi M., Nafisatus (Humanist Journal, 2022)
The waste bank is one of the containers that can solve the problems that people are experiencing. Garbage bank is a program by utilizing inorganic waste in order to get benefits and added value. Citizens' awareness and skills for managing or recycling waste by applying the principles of reduce, reuse, and recycle are important in solving waste problems through waste management from the source. The waste bank which is integrated with the 3R principle is implemented in the Rajawali Village, Jogosari Village, Pasuruan, East Java. The waste bank activity is a concept of collecting dry waste that has been sorted and has a feasibility that can improve the community's economy. In this case, the sorted inorganic waste is put into the warehouse in the waste bank, which can be used to be recycled into crafts such as flower pots from cup pop noodles, flower pots from mineral drinking water bottles and cup pop noodle caps as spots. foto., therefore it is necessary to empower youth in the Rajawali area through outreach activities to residents and youth in Rajawali. In addition, the need for cooperation with the RPL to realize progress in the Jogosari village. This garbage bank in the Jogosari sub-district has provided benefits to residents, especially direct benefits by reducing waste piles, making the environment clean and beautiful as well as residents' independence and creating inorganic waste processing skills. Integrated waste management can stimulate creativity and innovation from the community so as to improve the welfare of citizens.